Hepatitis C Virus Infection in Infants and Children from Argentina - Gismondi, María Inés (American Society for Microbiology, 2004)
Hepatitis C virus (HCV) infection is uncommon in children, and its natural history is still unknown. Our aim was to analyze exposure to HCV in 48 infants and children in Argentina and to evaluate consecutive samples in 26 of them to study the outcome of HCV infection in early stages. HCV viremia, as determined by reverse transcription-PCR (RT-PCR) from the 5′ untranslated region, showed continuously positive, occasionally positive, and negative patterns during follow-up. Restriction fragment length polymorphism was performed on RT-PCR-positive samples to evaluate HCV genotype. Genotype 1 turned out to be predominant, and no patient displayed a genotype shift during the observation period. Perinatal HCV infection was predominantly observed in patients born to mothers coinfected with HCV and human immunodeficiency virus. HCV viral load was detected by means of the AMPLICOR MONITOR, version 2.0, kit. No correlation was observed between HCV viral load and alanine aminotransferase and aspartate aminotransferase levels, although we detected a trend towards higher levels among patients displaying consecutive positive HCV RT-PCR results. Our results demonstrate that pediatric HCV infection is characterized by high viral loads and diverse HCV viremia patterns, independent of both age and route of transmission in the population under study. Further research is necessary to determine whether the high rate of HCV replication is related to virus variability or to host immune response.